Amphiphilic Janus magnetoplasmonic nanoparticles: pH-triggered self-assembly and fluorescence modulation - Lu, Derong (2022)
We report amphiphilicity-driven self-assembly of polymer-coated magnetoplasmonic Janus nanoparticles (JNP) that result in well-defined colloidal ensembles with controllable size, morphology, and dimension. The amphiphilic JNP building blocks were prepared by coating fluorescent dye-conjugated pH-responsive block copolymer (BCP) and hydrophilic polymers on plasmonic and magnetic side of the JNPs, respectively. Our results have demonstrated a direct correlation between the amphiphilicity of the JNP building block and the structural parameters of corresponding ensembles. It was found that the increase in the relative ratio of pH-responsive hydrophobic BCP and hydrophilic polymer grafts on two different parts of the JNP led to a morphological transition of assemblies from micellar cluster to lamellae to vesicle. It provides insight into the colloidal self-assembly of functional nanocrystal. Furthermore, the coating of well-defined BCP grafts on the gold nanoparticle (AuNP) of the JNPs offers the possibilities to finely tune the interparticle distance and precisely position dye molecules at the gap between neighboring JNPs in the ensembles, and the pH-sensitivity of the BCP allows to control the interparticle distance as a function of pH. Such dye-encoded magnetoplasmonic ensembles can serve as a well-defined platform to study the metal-fluorophore interaction, leading to an improved fundamental understanding of metal-enhanced fluorescence (MEF) process. The fluorescent magnetoplasmonic ensembles with defined morphologies (i.e., multimers and vesicles) are of broad interest for biomedical applications that require synergistic multifunctionalies such as theranostics and biosensors.